Impact of Monetary Policy and Commodities Market on Indonesia Composite Index (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research explores how several monetary policy and commodities market influence the movement of the Indonesia Composite Index (IHSG). Monetary policy is a set of actions taken by the central bank to regulate the currency and the economy, variable proxy is Rupiah Exchange Rate (Jisdor) and Indonesia Overnight Index Average (indONIA). Commodity markets are places where commodities are traded in physical or futures, the needs of the world still depend on certain commodities so that commodity prices can be related to economic conditions, variable proxy of comodities market is Gold, Crude Oil WTI, Coal Newcastle. Indonesia Composite Index is a index that reflects the price movements of all stocks listed on the Indonesia Stock Exchange. The study analyzes monthly data from January 2019 to December 2023, a period before the global disruption of the COVID-19 pandemic, the period during the pandemic and the gradual economic rebound that followed. Using multiple linear regression analysis, the study assesses the direction and statistical relevance of each variable’s effect on the Indonesia Composite Index. The results suggest that Indonesia Overnight Index Average and Crude Oil WTI prices have a significant positive impact on the index, the Rupiah Exchange Rate has a significant negative impact on the index, while Gold and Coal Newcastle have no significant impact on the index. These findings can serve as a useful reference for both investors and policymakers in understanding and anticipating movements in Indonesia’s capital market, especially in relation to monetary policy and global commodity trends.